RANCANG BANGUN SISTEM INFORMASI PENJUALAN CREAM SMILAX BERBASIS WEBSITE PADA PT.CENDRAWASIH EMAS KONSTRUKSI - Indrayani, Lilis; Zulkarnain, Zulkarnain; Rizky N S, M Nur; Mardewi, Mardewi Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2022)
Abstract Website-based Smilax cream sales information system at PT. Cenderawasi emas construction of an online and computerized sales system that is expected to be able to reach sales broadly making it easier to promote products to consumers' sales management. Making this information system uses the waterfall research method, in the stages of analysis, design, coding, testing to maintenance, this information system is made using the programming languages PHP, JavaScript, HTML, CSS, and MySQL. The system built can provide complete information about sales, product stock, and customers. So that the system that is built becomes a company tool for conducting sales activities. Based on the results of testing and implementation, it can be concluded that the Sales Information System for Cream Smilax at PT. Cendrawasih Emas Construction can be managed properly and meet the needs of the company.